Formulation of Antidandruff Shampoo From Skin Fruit Exctract and Press Water Lime (Citrus Hystrix DC.) with Various Concentrations - latirah latirah; Priyanto Dwi Nugroho (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Kaffir lime (Citrus hystrix DC.) Is an alternative for skin and hair care. This study aims to make an anti-dandruff shampoo from skin extracts and kaffir lime juice with various concentrations. The extract was made by maceration using ethyl acetate as a solvent with 20, 30 and 40% concentrations, respectively. The resulting extract is used as an active ingredient in the anti-dandruff shampoo formula. The research that resulted from anti ketomber shampoo from kaffir lime juice extract with a concentration of 20%, 30% and 40% includes specific weight (g / mL) 1.1213 ± 0.08, 1.0612 ± 0.01 and 1.1064 ± 0.04; foam height (cm) 8.00 ± 0.00, 7.97 ± 0.06 and 8.00 ± 0.00; pH 5.27 ± 0.02, 5.27 ± 0.02 and 5.69 ± 0.00; viscosity (Ns / m2) 35.00 ± 0.46, 24.05 ± 0.00 and 28.85 ± 0.00; water content 82.58, 82.52 and 83.91. All shampoo formulas showed very strong anti-dandruff activity to M.furfur and P.ovale (inhibition zone 35.67 ± 0.58 mm), but still lower than the inhibition zone of chemical-commercial shampoos (p <0.05). The lime juice shampoo formula was preferred by 34 panelists (p <0.05) in the hedonic test. also shows that all shampoo formulas have met the requirements based on the Indonesian National Standard.